2010
DOI: 10.1002/ajpa.21341
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to variation in baboon cranial morphology

Abstract: The development, function, and integration of morphological characteristics are all hypothesized to influence the utility of traits for phylogenetic reconstruction by affecting the way in which morphological characteristics evolve. We use a baboon model to test the hypotheses about phenotypic and quantitative genetic variation of traits in the cranium that bear on a phenotype’s propensity to evolve. We test the hypotheses that: 1) individual traits in different functionally and developmentally defined regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 106 publications
1
34
0
Order By: Relevance
“…ranging from r = 0.35 to 0.86), suggesting that, in general, the correlation between cranial distances and genetic distances is stronger in hominoids than in papionins. This result is also consistent with the findings of Roseman et al (2010) who found no differences in the heritability or conditional evolvability of different cranial regions in a captive population of baboons. This suggests that there may be few differences across the papionin cranium in terms of phylogenetic efficacy, with all regions being equally useful (or problematic) when attempting to reconstruct phylogenetic relatedness across taxa.…”
Section: Comparison With Patterns Found In Hominoid Taxasupporting
confidence: 92%
See 4 more Smart Citations
“…ranging from r = 0.35 to 0.86), suggesting that, in general, the correlation between cranial distances and genetic distances is stronger in hominoids than in papionins. This result is also consistent with the findings of Roseman et al (2010) who found no differences in the heritability or conditional evolvability of different cranial regions in a captive population of baboons. This suggests that there may be few differences across the papionin cranium in terms of phylogenetic efficacy, with all regions being equally useful (or problematic) when attempting to reconstruct phylogenetic relatedness across taxa.…”
Section: Comparison With Patterns Found In Hominoid Taxasupporting
confidence: 92%
“…In guenons, the morphology of several masticatory regions, the mandible, oral cavity, and zygomatic region, all yielded morphological matrices significantly correlated with genetic distances among taxa, but the non-masticatory chondrocranium did so with a higher correlation coefficient (Cardini and Elton, 2008). Therefore, despite the intuitive link between masticatory strain, plasticity, and homoplasy, the relationship between these factors is complex, and this phenomenon does not necessarily negatively affect the correspondence between cranial morphology and genetic patterns (von Cramon-Taubadel, 2009b;Roseman et al, 2010).…”
Section: Biomechanical Strainmentioning
confidence: 96%
See 3 more Smart Citations